A Decade of implementing the United Nations programme of action on small arms and light weapons : analysis of national reports - Parker, Sarah (UNIDIR GenevaCH, 2012)
Provides an analyis of national reports submitted by UN member states to the UN Secretary-General in response to the annual UN General Assembly resolutions on small arms. Covers reports from the adoption of the PoA in 2001 to 31 December 2011.